The Effect of Service Quality and Islamic Financial Education on Customer Growth and Risk Profile in Islamic Microfinance Institutions in Central Java - Priyana, Yana; Muhtadi, Muhamad Ammar; Hidayani, Lily (Westscience Press, 2024)
This study examines the impact of Service Quality and Islamic Financial Education on Customer Growth and Risk Profile within Islamic microfinance institutions operating in Central Java. A quantitative approach utilizing Structural Equation Modeling-Partial Least Squares (SEM-PLS) was employed to analyze data collected from 130 respondents using Likert scale surveys. The measurement model and structural model were evaluated to assess the relationships among the variables. The results indicate significant positive associations between both Service Quality and Islamic Financial Education with Customer Growth and Risk Profile. Service Quality emerged as a critical factor influencing Customer Growth, while Islamic Financial Education was found to enhance Risk Profile management. These findings underscore the importance of enhancing service delivery and financial literacy initiatives in promoting sustainable growth and risk management in Islamic microfinance.